Investigation of perceived challenges and benefits of using data warehouse : a case study of education sector - Ademola, Adebiyi Lookman (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2012)
Increase in the use of Information and Communication Technology (ICT) has made it to become an important tool to achieve numerous goals in several sectors of the economy. It has developed so many of today's innovations and offers large potential for further innovations and developments, that will bring further changes to social life in the future. ICT provides variety of services that provides different technology such as data warehouse. Data warehouse is currently one of the most powerful technology innovations in recent years to support organization-wide decision making, which has become a key component of ICT. A data warehouse is organized around major subjects, such as customer, supplier, product, students, and staffs of organizations and sales which focus on the modeling and analysis of data for decision makers. Thus, the purpose of this research is to investigate despite all the challenges or barriers, the benefits that influence the usage of data warehouse in Education sector. The study usedInternational Islamic University, Malaysia (IIUM) as a case study by adopting a mixed method research approach, to conduct interview sessions with the IT services provider (Information Technology Division), few principal staffs, and conducting a survey among staffs of IIUM from administrative staffs upwards and some selected few staffs that handledaily tasks with IIUM data. The interviews were transcribed to extract important facts got from the interviewees, while SPSS software was used to systematically analyze all data obtained from the respondents so as to generate statistical information and detail analyses of the survey results. The quantitative and qualitative results were triangulated so as to discover the numerous challenges that are being faced without using data warehouse in order to explore the benefits that influence the use of data warehouse to eradicate these challenges were investigated.